Peran Pembina Asrama dalam Meningkatkan kedisiplinan Santriwati di Asrama I Pondok Pesantren Bequranic Bengkalis - Ahla, Asyifa; Robiah (STAIN Bengkalis, 2024)
This type of research is descriptive qualitative, and uses field research. The data source forthis research is the female students of dormitory I at the Bequranic Bengkalis Islamic BoardingSchool, which consists of 111 female students. Furthermore, data collection in this research usedsystematic sampling techniques and the results of data collection in this research were analyzedusing qualitative data analysis techniques. Based on the research findings, it can be concluded thatthe results of this research are in accordance with the problem formulation, namely the role ofdormitory supervisors in improving discipline in dormitory I of the Bequranic Bengkalis Islamicboarding school, the results of this research show. That the role of dormitory supervisors inimproving the discipline of female students is very important. As well as the existence of dormitorysupervisors as second parents in improving student discipline, the methods in this research include:advice method, example method, and habituation method. The obstacles experienced by dormitorysupervisors in improving the discipline of female students are a lack of maximum cooperationbetween parents and dormitory supervisors, a lack of motivation and enthusiasm for female studentsin studying, and less intensive supervision of regulations. Meanwhile, the solution taken by thedormitory supervisors to improve female students' discipline is that the dormitory supervisorscollaborate with the parents of the female students, providing advice and role models to the femalestudents. As well as giving punishment to female students who violate the rules of the BequranicBengkalis Islamic boarding schoolKeywords: Dormitory Supervisor, and Discipline